Catatan baru hama penting, Frankliniella intonsa (Trybom) (Thysanoptera: Thripidae) pada tanaman stroberi di Desa Alamendah, Kecamatan Rancabali Kabupaten Bandung, Jawa Barat - Ciptadi Achmad Yusup; Dewi Sartiami (Perhimpunan Entomologi Indonesia, 2015)
Strawberry is a new crop in Indonesia, and it has been developed because of its high demands. Thrips is one of the strawberry pest that can reduce quality and quantity strawberry productions. The research was conducted in Alamendah-Rancabali Village, Bandung District from March to August 2012. Thrips species that attack strawberry in Alamendah Village dominated by Frankliniella intonsa (Trybom). Other thrips that were found on plants surround strawberry field is Thrips palmi and Microcephalothrips abdominalis. Both of these thrips are found on tomatoes, potatoes, leek, blackberries, weeds (Amaranthus sp. and Ageratum haustonianum). The complete stadia of F. intonsa were found on strawberry flowers. Population densities in the field were found to be between 1.8 to 2.3 individual/flower. Around 68.4%-82.2% of the fields are are infested with F. intonsa. Based on test of F. intonsa attack ability on strawberry plant, the result shows 43% of fruit that harvested is malformed on tips of fruits. Therefore, F. intonsa is potential to become a important pest of strawberry plant.